Vital capacity and COPD: the Swedish CArdioPulmonary bioImage Study (SCAPIS) - Torén K; Olin AC; Lindberg A; Vikgren J; Schiöler L; Brandberg J; Johnsson Å; Engström G; Persson HL; Sköld M; Hedner J; Lindberg E; et al. (International Journal of COPD, 2016)
Kjell Torén,1 Anna-Carin Olin,1 Anne Lindberg,2 Jenny Vikgren,3 Linus Schiöler,1 John Brandberg,3 Åse Johnsson,3 Gunnar Engström,4 H Lennart Persson,5 Magnus Sköld,6 Jan Hedner,7 Eva Lindberg,8 Andrei Malinovschi,8 Eeva Piitulainen,9 Per Wollmer,9 Annika Rosengren,10 Christer Janson,8 Anders Blomberg,2 Göran Bergström10 1Section of Occupational and Environmental Medicine, Department of Molecular and Clinical Medicine, Institute of Medicine, Sahlgrenska Academy, University of Gothenburg, Gothenburg, 2Department of Public Health and Clinical Medicine, Division of Medicine/Respiratory Medicine, Umeå University, Umeå, 3Department of Radiology, Institute of Clinical Sciences, Sahlgrenska Academy, University of Gothenburg, Gothenburg, 4Department of Clinical Science, Malmö, Lund University, Lund, 5Department of Respiratory Medicine and Department of Medicine and Health Sciences, Linköping University, Linköping, 6Respiratory Medicine Unit, Department of Medicine Solna, Center for Molecular Medicine, Karolinska Institutet, Stockholm, 7Department of Internal Medicine/Lung Medicine, Institute of Medicine, Sahlgrenska Academy, University of Gothenburg, Gothenburg, 8Department of Medical Sciences, Clinical Physiology and Respiratory, Allergy and Sleep Research, Uppsala University, Uppsala, 9Department of Translational Medicine, Lund University, Malmö, 10Department of Molecular and Clinical Medicine, Institute of Medicine, Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden Background: Spirometric diagnosis of chronic obstructive pulmonary disease (COPD) is based on the ratio of forced expiratory volume in 1 second (FEV1)/vital capacity (VC), either as a fixed value <0.7 or below the lower limit of normal (LLN). Forced vital capacity (FVC) is a proxy for VC. The first aim was to compare the use of FVC and VC, assessed as the highest value of FVC or slow vital capacity (SVC), when assessing the FEV1/VC ratio in a general population setting. The second aim was to evaluate the characteristics of subjects with COPD who obtained a higher SVC than FVC.Methods: Subjects (n=1,050) aged 50–64 years were investigated with FEV1, FVC, and SVC after bronchodilation. Global Initiative for Chronic Obstructive Lung Disease (GOLD) COPDFVC was defined as FEV1/FVC <0.7, GOLDCOPDVC as FEV1/VC <0.7 using the maximum value of FVC or SVC, LLNCOPDFVC as FEV1/FVC below the LLN, and LLNCOPDVC as FEV1/VC below the LLN using the maximum value of FVC or SVC.Results: Prevalence of GOLDCOPDFVC was 10.0% (95% confidence interval [CI] 8.2–12.0) and the prevalence of LLNCOPDFVC was 9.5% (95% CI 7.8–11.4). When estimates were based on VC, the prevalence became higher; 16.4% (95% CI 14.3–18.9) and 15.6% (95% CI 13.5–17.9) for GOLDCOPDVC and LLNCOPDVC, respectively. The group of additional subjects classified as having COPD based on VC, had lower FEV1, more wheeze and higher residual volume compared to subjects without any COPD.Conclusion: The prevalence of COPD was significantly higher when the ratio FEV1/VC was calculated using the highest value of SVC or FVC compared with using FVC only. Subjects classified as having COPD when using the VC concept were more obstructive and with indications of air trapping. Hence, the use of only FVC when assessing airflow limitation may result in a considerable under diagnosis of subjects with mild COPD. Keywords: obstructive, epidemiology, general population, air trapping, spirometry, slow vital capacity, asthma